Understanding the mechano and chemo response of retinoblastoma tumor cells - Gopal Divya; Ramani Madhura; Vikas Khetan; Pukhraj Rishi; Janakiraman Narayanan (Elsevier, 2022)
Introduction: Cellular homeostasis with its environment is bidirectional and dynamic in nature. Extracellular matrix plays an important role in retinoblastoma tumor cell's response to chemotherapeutic drugs. The present study was designed to investigate the effect of mechanotransduction along with the chemotherapeutic effect on RB cells grown on three-dimensional matrices. Methods: Matrigels of varying stiffness (low and high) were prepared and characterized. Drug sensitivity of RB cells on various matrigel stiffness was measured using cytotoxicity (MTT) assay and IC50 value was found for carboplatin and etoposide. Further, the effect on the proliferation and migration of RB cells in various stiffness matrigels was investigated. Findings: The results showed that drug sensitivity decreased with an increase in matrix stiffness when compared to RB cells grown in suspension. In higher stiffness, the drug sensitivity decreases with an increase in cell proliferation. Data from a gene expression study revealed that Vinculin was variably regulated between metastatic and non-metastatic tumor cells, and upregulated RhoA was altered in different stiffness gradient matrigel during drug treatment. Interpretation: These results enhance the understanding of the fundamental molecules responding to drug sensitivity in a stiffness-altering environment. Additionally, it provides a new avenue for understanding how RB cells respond to chemotherapeutic intervention.